A Pronounced Spike in Ocean Productivity Triggered by the Chicxulub Impact. Issue 12 (17th June 2021) - Brugger, Julia; Feulner, Georg; Hofmann, Matthias; Petri, Stefan
Abstract: There is increasing evidence linking the mass‐extinction event at the Cretaceous‐Paleogene boundary to an asteroid impact near Chicxulub, Mexico. Here we use model simulations to explore the combined effect of sulfate aerosols, carbon dioxide and dust from the impact on the oceans and the marine biosphere in the immediate aftermath of the impact. We find a strong temperature decrease, a brief algal bloom caused by nutrients from both the deep ocean and the projectile, and moderate surface ocean acidification. Comparing the modeled longer‐term post‐impact warming and changes in carbon isotopes with empirical evidence points to a substantial release of carbon from the terrestrial biosphere. Overall, our results shed light on the decades to centuries after the Chicxulub impact which are difficult to resolve with proxy data. Plain Language Summary: The sudden disappearance of the dinosaurs and many other species during the end‐Cretaceous mass extinction 66 million years ago marks one of the most profound events in the history of life on Earth. The impact of a large asteroid near Chicxulub, Mexico, is increasingly recognized as the trigger of this extinction, causing global darkness and a pronounced cooling. However, the links between the impact and the changes in the biosphere are not fully understood. Here, we investigate how life in the ocean reacts to the perturbations in the decades and centuries after the impact. We find a short‐lived algal bloom caused by the upwelling of nutrients from the deep ocean and nutrient input from the impactor. Key Points: We investigate the effects of sulfate aerosols, carbon dioxide and dust produced by the Chicxulub impact on climate and the marine biosphere Nutrients from the deep ocean and the projectile induce a short increase in marine primary productivity after the impact‐induced darkness Simulated post‐impact warming and carbon isotope changes indicate substantial emissions of carbon from the terrestrial biosphere